KELAYAKAN LEAFLET PRAKTIKUM PEMBUATAN SIRUP JAHE PADA SUBMATERI PERAN TUMBUHAN DI BIDANG EKONOMI KELAS X SMA - Chaniago, Aulia Rahma; Daningsih, Entin; ., Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aimed to determine the feasibility of leaflet making of ginger syrup (Zingiber officinale) as a learning medium on sub chapter the role of plants in economics class X high school. This research was a descriptive research. The data were collected using a validation instrument. Validation was done by 5 validator, 2 validator was a lecturer of biology education, while 3 other validator was a biology teacher of class X high school using the 2013 curriculum in Pontianak city. The result of  leaflet validation with 14 criteria obtained CVI value equal to 0.99 in accordance with minimum CVI value of Lawshe for 5 validator the value of 0.99. So that media leaflet was categorized valid and declared feasible as learning media on sub chapter role of plants in economics class X high school.  Keywords:  leaflet, ginger syrup, role of plants in economics class X high  school